Charge Effects in PCP Pincer Complexes of NiII bearing Phosphinite and Imidazol(i)ophosphine Coordinating Jaws: From Synthesis to Catalysis through Bonding Analysis. Issue 48 (9th October 2015) - Vabre, Boris; Canac, Yves; Lepetit, Christine; Duhayon, Carine; Chauvin, Remi; Zargarian, Davit
Abstract: This contribution reports on a new family of Ni II pincer complexes featuring phosphinite and functional imidazolyl arms. The proligands R PIMC H OP R′ react at room temperature with Ni II precursors to give the corresponding complexes [( R PIMCOP R′ )NiBr], where R PIMCOP R =κ P, κ C, κ P ‐2‐(R′2 PO), 6‐(R2 PC3 H2 N2 )C6 H3 , R= i Pr, R′= i Pr (3 b, 84 %) or Ph (3 c, 45 %). Selective N ‐methylation of the imidazole imine moiety in3 b by MeOTf (OTf=OSO2 CF3 ) gave the corresponding imidazoliophosphine [( i Pr PIMIOCOP i Pr )NiBr][OTf], 4 b, in 89 % yield ( i Pr PIMIOCOP i Pr =κ P, κ C, κ P ‐2‐( i Pr2 PO), 6‐( i Pr2 PC4 H5 N2 )C6 H3 ). Treating4 b with NaOEt led to the NHC derivative [(NHCCOP i Pr )NiBr], 5 b, in 47 % yield (NHCCOP i Pr =κ P, κ C, κ C ‐2‐( i Pr2 PO), 6‐(C4 H5 N2 )C6 H3 )). The bromo derivatives3–5 were then treated with AgOTf in acetonitrile to give the corresponding cationic species [( R PIMCOP R )Ni(MeCN)][OTf] [R=Ph, 6 a (89 %) or i Pr, 6 b (90 %)], [( R PIMIOCOP R )Ni(MeCN)][OTf]2 [R=Ph, 7 a (79 %) or i Pr, 7 b (88 %)], and [(NHCCOP R )Ni(MeCN)][OTf] [R=Ph, 8 a (85 %) or i Pr, 8 b (84 %)]. All new complexes have been characterized by NMR and IR spectroscopy, whereas3 b, 3 c, 5 b, 6 b, and8 a were also subjected to X‐ray diffraction studies. The acetonitrile adducts6 –8 were further studied by using various theoretical analysis tools. In the presence of excess nitrile and amine, the cationic acetonitrile adducts6 –8 catalyze hydroamination of nitriles to give unsymmetrical amidines with catalytic turnover numbers of up to 95. Abstract : Turning nitriles into amidines : Hydroamination of benzonitrile with aliphatic primary or secondary amines is catalyzed by cationic Ni II species ligated by a new family of PCP pincer‐type ligands; PIMCOP, PIMIOCOP, and NHCCOP (shown in scheme). The new Ni II pincer complexes are characterized by X‐ray diffraction and NMR and IR spectroscopy and further studied by theoretical methods.